DESIGNING ALVO GAME FOR ELEMENTARY SCHOOL STUDENTS - Nyani Fatmawati; Safra Apriani Zahraa; Abdul Malik Ahmad (INOVISH JOURNAL, 2019)
In learning English, there are several skills that should be learned by students such as listening, speaking, reading and writing. The students are expected to be able to master all language skills of English to communicate. In order to communicate there are components that the students must be able to acquire. Vocabulary is important to learn by students. One of ways to learn vocabulary is through a game. An Alvo Game was adapted from Game Guess Image and Scrabble game. The purpose of this study is to make Alvo Game to for elementary school students. The result of this study was a set of Alvo Game consists of plywood in which that there are twenty-nine double of alphabet and thirty pictures. The evaluation showed that it was suitable for elementary school students. By using this game, the students can learn vocabulary in a more interesting and attractive way.